2003
DOI: 10.1046/j.1440-1746.2003.03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different doses of furazolidone with amoxicillin and omeprazole on eradication of Helicobacter pylori

Abstract: The regimen with a non-reduced dose of furazolidone in combination with amoxycillin and omeprazole was effective when the patients tolerated the drugs and completed the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
0
34
1
1
Order By: Relevance
“…In the present study, despite a comparable incidence of adverse effects during treatment, only three patients had severe symptoms demanding treatment discontinuation. Lower doses of furazolidone could decrease the incidence of undesirable symptoms, but this strategy can also lead to a lower eradication rate [22,28,29] . The prevalence of smokers was similar to that in the Brazilian population and no significant differences in the results were observed when analyzing the number of previous treatments, gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, despite a comparable incidence of adverse effects during treatment, only three patients had severe symptoms demanding treatment discontinuation. Lower doses of furazolidone could decrease the incidence of undesirable symptoms, but this strategy can also lead to a lower eradication rate [22,28,29] . The prevalence of smokers was similar to that in the Brazilian population and no significant differences in the results were observed when analyzing the number of previous treatments, gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the low dose of furazolidone used was different from our study. Roghani et al (9) showed that furazolidone in combination with amoxicillin and omeprazole should be used as a higher dose. They concluded that, although serious adverse effects were less frequent with the lowdose regimen, the intention-to-treat eradication rate was not acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Furazolidone offer the advantage of low cost, but unfortunately, more adverse effects influence the drug efficacy (9,10). It should be considered that triple therapy with amoxicillin, furazolidone and omeprazole (AFO) is more tolerable due to fewer required drugs and is more economically affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Both protocols had ideal results with fewer side ef- fects [23,48] . Furazolidone has also been used in triple therapies in Iran [21,[80][81][82][83] . Five studies have investigated the effects of 4-, 7-and 14-d Furazolidone-containing triple therapies, but only a 7-d protocol, in which a probiotic had been added to the regimen, could achieve > 90% PP eradication rate [82] .…”
Section: Furazolidonementioning
confidence: 99%
“…Furazolidone has low cost and is readily available in developing countries. When it was administered in low doses (50 mg BD), the efficacy of regimen was shown to be very low [83] . On the other hand, when administered in high doses (200 mg BD), if tolerated, the efficacy of regimen was comparable to that of Clarithromycin-containing regimens [79] .…”
Section: Furazolidonementioning
confidence: 99%